2018
DOI: 10.1038/s41598-018-26106-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic risk score of common genetic variants for impaired fasting glucose and newly diagnosed type 2 diabetes influences oxidative stress

Abstract: We tested the hypothesis that the cumulative effects of common genetic variants related to elevated fasting glucose are collectively associated with oxidative stress. Using 25 single nucleotide polymorphisms (SNPs), a weighted genetic risk score (wGRS) was constructed by summing nine risk alleles based on nominal significance and a consistent effect direction in 1,395 controls and 718 patients with impaired fasting glucose (IFG) or newly diagnosed type 2 diabetes. All the participants were divided into the fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 54 publications
1
7
2
Order By: Relevance
“…To our knowledge, the present study is the first to report the effects of GCKR variants rs1260326 and rs1260333 on TG levels in a Korean population. In Korean populations, rs1260326 was associated with the risk of IFG and type 2 diabetes [34] and total and low-density lipoprotein (LDL) cholesterol in children [33]. Rs1919127 and rs1919128 at C2orf16 gene on chromosome 2p23.3 were associated with elevated TG level in our study.…”
Section: Discussionsupporting
confidence: 49%
“…To our knowledge, the present study is the first to report the effects of GCKR variants rs1260326 and rs1260333 on TG levels in a Korean population. In Korean populations, rs1260326 was associated with the risk of IFG and type 2 diabetes [34] and total and low-density lipoprotein (LDL) cholesterol in children [33]. Rs1919127 and rs1919128 at C2orf16 gene on chromosome 2p23.3 were associated with elevated TG level in our study.…”
Section: Discussionsupporting
confidence: 49%
“…Nevertheless, there are also some discrepancies between this study and previous research. A previous study reported that DGKB (rs2191349) and GCK (rs1799884 and rs4607517) were significantly associated with IFG and T2DM in the Korean population [9], but no strong association was identified for those polymorphisms in the present study. Sara Moradipoor et al [58] evaluated the gene expression levels in prediabetes and T2DM and observed that 17 genes displayed substantially higher expression in the T2DM group than in the prediabetes group, indicating differences in gene expression between prediabetes and T2DM conditions.…”
Section: Discussioncontrasting
confidence: 88%
“…According to a GWAS and a previous study, nine SNPs were established at IFG and T2DM loci showing the strongest associations with glycemic traits [9]. SNP chip analysis was performed using an Axiom ® Korean Biobank Array 1.1.…”
Section: Snp Selection and Snp Chip Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it was strongly and significantly associated with the concentrations of urinary 8-epi-PGF2α and MDA, the lipid peroxidation biomarker and oxidative stress. [ 8 ]…”
Section: Introductionmentioning
confidence: 99%